2011
DOI: 10.2739/kurumemedj.58.95
|View full text |Cite
|
Sign up to set email alerts
|

Successful Treatment of T4 Renal Cell Carcinoma After a Neoadjuvant Targeted Therapy Using Sunitinib: Report of a Case

Abstract: Summary:Since the introduction of targeted therapy, treatment of metastatic renal cell carcinoma (RCC) has undergone dramatic changes. Responses to targeted therapy within the primary tumor and metastatic lesions are novel findings not seen with immunotherapeutic-based strategies. We report here a case of T4 RCC in which cytoreductive nephrectomy became possible after a neoadjuvant targeted therapy using sunitinib. Our experience with the present case suggests that targeted therapy in the neoadjuvant setting m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2014
2014
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…However, the surgical benefits after NT in mRCC have generally been observed during the immunotherapy era. While the use of preoperative TT in the setting of locally advanced or metastatic RCC (mRCC) remains in its preliminary stages, with only a few retrospective studies and case reports (2161718), there is a growing body of evidence that may support its role in a select group of patients (8). Therefore, the present study is significant because few studies have evaluated neoadjuvant TT in Asian populations (19), and, to the best of our knowledge, this is the first and only study of NT using a targeted agent in Korean patients with mRCC.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the surgical benefits after NT in mRCC have generally been observed during the immunotherapy era. While the use of preoperative TT in the setting of locally advanced or metastatic RCC (mRCC) remains in its preliminary stages, with only a few retrospective studies and case reports (2161718), there is a growing body of evidence that may support its role in a select group of patients (8). Therefore, the present study is significant because few studies have evaluated neoadjuvant TT in Asian populations (19), and, to the best of our knowledge, this is the first and only study of NT using a targeted agent in Korean patients with mRCC.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, 2-cycle sunitinib therapy was selected to evaluate the tolerability and efficacy of NT (31617). No cases of perioperative morbidity or major intraoperative complications were observed during this study.…”
Section: Discussionmentioning
confidence: 99%
“…After 4 courses of chemotherapy, the tumor had shrunk to 44% and 54% on the right and left, respectively, with a consequent reduction in Renal Score. Kousuke Ueda et al (13), however, reported a case of a 70-year-old man with a clear cell carcinoma T4 N0 M1 treated with chemotherapy with Sunitinib 50 mg/day, who after 4 courses had a 28% reduction in tumor size, together with a reduction in hepatic invasion and disappearance of pulmonary metastases, making the surgical treatment easier. Shuch et al (14) demonstrated an effective response to neoadjuvant chemotherapy in three patients, for whom surgery was initially contraindicated due to the stage of disease.…”
Section: Discussionmentioning
confidence: 99%
“…These tumors are often associated with aggressive features such as Fuhrman grade 3 or 4, sarcomatoid dedifferentiation and lymphovascular invasion. Although several studies have shown promising results with neoadjuvant therapy in the setting of large surgical tumor burden [9-11], such pathologic features ultimately result in an intrinsically aggressive behavior with adjacent organ invasion, potentially leading to “unresectable” disease in spite of the best targeted therapies available.…”
Section: Introductionmentioning
confidence: 99%